Resilience investments under climate change: a regional case study in Southeast Australia - Box, Paul J.; Xenarios, Stefanos; Wise, Russell M.; Heinmiller, Peter; Sarker, Chandrama; Pert, Petina L.; Meharg, Seona; Edwards, Gemma; Gorddard, Russell; Azevedo, Sofia; Flett, Dianne; Mesic, Nic; et al. (Frontiers in Environmental Science, 2025)
Many regions in Australia have experienced substantial damage to their natural, social, and environmental infrastructure from natural hazards. The scale and impact of these events have increased in recent decades due to the growing exposure and vulnerability of larger populations, economic activities, and infrastructure (both built and natural), as well as the intensification of natural hazards induced by climate change. Despite the increasing challenges, there is still limited investment in building resilience. Moreover, many local governments throughout Australia lack the necessary technical capabilities, knowledge, and funding to ensure the reliable ongoing delivery of essential services to communities, much less to identify, assess, and implement resilience interventions. The implementation becomes more challenging in the case of Nature-based Solutions for disaster resilience and climate adaptation where there are significant gaps in understanding and evidence of their effectiveness in the short and long term. This study proposes a discursive, place-based, and cross-scale approach to overcoming these challenges and enabling councils to develop resilient investment cases (RICs) as part of regional planning processes involving local governments, research institutions, and private sector stakeholders. The approach involves: collectively identifying values and vulnerabilities in a hazard-prone region in south-east Australia; prioritizing focal infrastructure asset types for investigation, in this case transport but relevant to all forms of critical infrastructure including nature; identifying suitable interventions for resilience planning under scenarios of change; and formulating RICs by assessing the effectiveness, costs, and benefits of bundles of resilience interventions under scenarios of change. We present the approach as applied in the Bega Valley Local Government Area which is highly exposed and vulnerable to impacts from natural hazards. Insights and lessons from the case study are applicable to a range of critical infrastructure types, including nature-based solutions (green and blue infrastructure), as well as other regions in Australia and abroad that require resilient investment planning.